Formulation of New Equation to Estimate Productivity Index of Horizontal Wells - Ghanim M. Farman; Maha Raouf Abdulamir (Iraqi Journal of Chemical and Petroleum Engineering, 2014)
Significant advances in horizontal well drilling technology have been made in recent years. The conventional productivity equations for single phase flowing at steady state conditions have been used and solved using Microsoft Excel for various reservoir properties and different horizontal well lengths. The deviation between the actual field data, and that obtained by the software based on conventional equations have been adjusted to introduce some parameters inserted in the conventional equation. The new formula for calculating flow efficiency was derived and applied with the best proposed values of coefficients ψ=0.7 and ω= 1.4. The simulated results fitted the field data. Various reservoir and field parameters including lateral horizontal length of the horizontal well (L), Skin factor (S), ratio of the vertical to horizontal permeability of the formation (KV/KH), and the vertical thickness of the productive zone (h) were studied and verified to generalize the suggested equation to estimate the horizontal well productivity indices for various reservoir kinds. This led to creating a new formula of flow efficiency equation that could be applied in AHDEB field.